Petanda Bahasa Laki-Laki dan Perempuan dalam Konteks Bahasa - Sabriandi Erdian (Politeknik Negeri Padang, 2013)
Halliday (1989) and Dell Hymes stated that the signifier of male and female language in the process of communication can be known from the elements, such as condition, participants, intention and effect of communication, key, channel, style and norm in reciprocal interaction. By using the signifiers used, the semiotics appears naturally and the symbols become the signifier and signified